Western Experience of Hepatolithiasis: Clinical Insights from a Case Series in a Tertiary Center - Natale Calomino; Ludovico Carbone; Engjell Kelmendi; Stefania Angela Piccioni; Gianmario Edoardo Poto; Giulio Bagnacci; Luca Resca; Annalisa Guarracino; Sergio Tripodi; Bina Barbato; Stefano Brillanti; Franco Roviello; et al. (Medicina)
Background and Objectives: Hepatolithiasis (HL), or intrahepatic bile duct stone disease, shows regional variation and is a rare condition in Western countries. While cases from East Asia are often linked to chronic biliary infections and brown pigment stones, Western HL more frequently involves cholesterol or black pigment stones, typically in the context of prior cholecystectomy, biliary interventions, or congenital anomalies. The disease is generally associated with significant morbidity, including recurrent cholangitis, biliary strictures, and risk of cholangiocarcinoma. This study aimed to characterize HL disease in an Italian case series. Materials and Methods: We retrospectively reviewed 1450 patients with biliary stone disease treated between 2010 and 2024. HL was diagnosed in 14 patients (0.96%). Clinical records, imaging (ultrasound, CT, magnetic resonance cholangiopancreatography—MRCP, cholangiography), bile cultures, and stone composition (categorized as cholesterol, brown pigment, black pigment, or mixed using FTIR/XRD) were analyzed. Results: Among the 14 patients (mean age: 60.1 years; 64.3% female), 71.4% presented with recurrent cholangitis, while 28.6% were asymptomatic. Stones were left-sided in 57.1%, right-sided in 21.4%, and bilateral in 21.4%. Stone composition was cholesterol/mixed in 50%, brown pigment in 35.7%, and black pigment in 14.3%. Risk factors for bile stasis were present in 71.4% of cases. Bile cultures (available in nine cases) were positive in 77.8%. MRCP was highly effective for diagnosis. Hepatectomy achieved complete resolution in 35.7% of patients with unilobar disease; endoscopic/percutaneous therapy had a 44.4% recurrence rate. Interestingly, no cholangiocarcinoma was observed over a median follow-up of 4.8 years. Conclusions: Western HL is a rare, heterogeneous disease with distinct features. Cholesterol-predominant, infection-negative cases suggest a metabolic or surgical etiology. Hepatectomy offers durable outcomes in unilobar disease. Advanced imaging (MRCP, cholangioscopy) and personalized strategies are key to effective management.